2008
DOI: 10.1093/schbul/sbn091
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Social-Cognitive Deficits in Schizophrenia With the Mayer-Salovey-Caruso Emotional Intelligence Test

Abstract: The emotion management subscale of the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) has recently been recommended by the National Institute of Mental Health Measurement and Treatment Research to Improve Cognition in Schizophrenia committee as the sole measure of social cognition for trials of cognitive enhancement in schizophrenia, yet the psychometric properties of this subscale and the larger instrument in schizophrenia patients have not been thoroughly examined. This research presents a psychom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
109
4
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 41 publications
15
109
4
2
Order By: Relevance
“…Interestingly, previous EFA studies in the SC domain of schizophrenia patients have found similar SC derived factors that we did (Eack, Greeno, et al, 2010;P. H. Lysaker et al, 2013;Ziv et al, 2011).…”
Section: Demographics: Hippocampus and Amygdala Shape Analysissupporting
confidence: 84%
“…Interestingly, previous EFA studies in the SC domain of schizophrenia patients have found similar SC derived factors that we did (Eack, Greeno, et al, 2010;P. H. Lysaker et al, 2013;Ziv et al, 2011).…”
Section: Demographics: Hippocampus and Amygdala Shape Analysissupporting
confidence: 84%
“…Table 2 provides a list of the selected measures along with citation information and number of nominations. Of note, the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) 51 received 8 nominations; however, because the basic psychometric properties of the MSCEIT have already been established, 52,53 it was not considered for inclusion in this portion of the project.…”
Section: Expert Surveysmentioning
confidence: 99%
“…3 Emotional intelligence captures broader socioemotional functioning ranging from facial emotion perception to higher level processes including understanding, inferring, and effectively regulating emotional states, 25 and SCZ participants have shown consistent deficits in emotional intelligence. 3,26,27 In addition, a recent neuroimaging study showed that poorer emotional intelligence in SCZ was associated with abnormal functional coupling of the visual cortex with anterior cingulate cortex during a social appraisal task. 28 Although early visual processing was not directly assessed in this study, it provides evidence for an important connection between basic visual processing and higher level social functioning in the disorder, calling for further investigations.…”
Section: The Present Studymentioning
confidence: 99%
“…29 For social cognition, gaze perception and emotional intelligence were selected to represent a range of levels of socioemotional information processing with documented relevance to SCZ. 1,3,26,27 We hypothesized that (1) SCZ participants would show poorer visual integration than HC; (2) visual integration would be associated with social cognition (including gaze perception and emotional intelligence) in SCZ; and (3) variances in the social cognitive measures due to visual integration would be comparable to and overlap with those due to diagnosis group.…”
Section: The Present Studymentioning
confidence: 99%